Fitness of Echinochloa crusgalli var. mitis biotypes susceptible and resistant to imazapyr + imazapic herbicide - Bonow, Joice Fernanda Lübke; Lamego, Fabiane Pinto; Andres, André; Nogueira, Eduardo (Comunicata Scientiae, 2019)
The continuous use of herbicides with the same mechanism of action has caused the selection of resistant weed biotype that may present differences in fitness when compared with susceptible biotype. The objective of the present study was to identify and distinguish the fitness of barnyardgrass biotypes resistant and susceptible to imazapyr + imazapic herbicide under controlled and noncompetitive conditions. For that, there were used barnyardgrass biotype susceptible (ECH1 and ECH38) and resistant (ECH14 and ECH44) to ALS inhibitors, collected at Pelotas/RS and Rio Grande/RS cities, respectively, in experiment installed in a greenhouse in a completely randomized experimental design during the months from October to December 2015. The biotype were evaluated during the period of 15 to 120 days after the emergence related to plant height, foliar area, shoot dry matter mass and root dry matter mass. The results showed insignificant differences between the biotypes during the development of the plants. The susceptible biotype ECH44 showed a higher number of panicles per plant and seeds along with the resistant ECH1. There is variability among Echinochloa crusgalli var. mitis biotypes resistant and susceptible to ALS inhibitors, indicating an absence in fitness penalty caused by resistance when cultivated without the selection of pressure (herbicide).